As territorialidades das mulheres na agroecologia e a construção da certificação participativa na Rede Ecovid - Eduardo, Daiane Carla Bordulis (2024)
The transformations carried out within family and peasant farming in recent years have awakened the need for studies on its new facets and on the current territorial dynamics of these ways of producing and socially organizing themselves in the countryside. In the context of family farming, one of the segments that has stood out is Agroecology as it is considered a proposal for territorial development with potential for inclusion, income generation and permanence or deterritorialization of people in the countryside. By providing visibility to female work, Agroecology also favors more balanced gender relations and rearrangements in the social and production dynamics of family farming. The objective of this work was to analyze how and under what circumstances the territorialities linked to Agroecology enhance the protagonism of women, considering their insertions in the different spatial, productive and organizational dynamics of the Ecovida Agroecology Network. The methodology used was based on qualitative research, carried out through bibliographic analysis and the collection of primary and secondary information, consultation of files and documents from the Ecovida Network, interviews with a semi-structured script and also participative action research. Participatory certification enables women to take a leading role, thus strengthening their territorialities based on the various scales of territorial action. They construct their concrete modes of existence, based on the forms and conditions with which they spatially project their power relations. This is a certification methodology that has the potential to include women; in other audit certification systems, the focus is only on the organic conformity of production processes. As learned, even though agroecological agriculture has allowed an opening for a debate beyond productive issues, there has been a need for women to struggle to build their spaces within Agroecology, that is, adherence to these different precepts is not automatic and immediate.: economically viable, socially fair and environmentally balanced. With this, we highlight our understanding that the agroecological transition needs to be multidimensional, not only economic or environmental, but also political and cultural.